Parol Evidence Rule Doctrin as the Limitation for the Parties in Submitting Evidence Before the Court - Praditha Suraja Wahana (Universitas Airlangga, 2018)
Contracts that made by the parties as the basis of engagement are the perfect and strongest proof or facts when there is a contract dispute between the parties which made it. To be reliable then the contents of the contract must be guaranteed the truth. The doctrine parol evidence rule plays a big role to make that happen. This doctrine works primarily in the evidentiary stage of the trial by preventing the submission of evidences which is classified as an extrinsic evidence to be submitted to the courts, since such evidences is highly questionable and therefore potentially fraudulent. However, the application of a rigid and absolute parol evidence rule may also lead to unfavorable situations for contracting parties, so under certain conditions such doctrine by the judge may be overruled. The doctrine if implemented in Indonesia will be support in enforcement and application the articles in BW (Indonesian Civil Code), especially Articles 1342 and Article 1350 BW. Moreover, the application of this doctrine can also improve judicial efficiency in terms of time, cost and personnel. The parties will be benefited from the application of this doctrine, for instance it will protect the truth of the contents of the contract so as to prevent doubts about the contracts they have made and encourage the parties to promote the prudentially principle.